Meningkatkan Pengetahuan Remaja dalam Penelitian Sosial di Masa Pandemi - Nandi Kurniawan; Saipiatuddin Saipiatuddin; Achmad Hidayaht (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
This article is the result of community service activities that aim to increase adolescent knowledge in social research, especially during the Covid 19 pandemic. The form of activity is in the form of webinars which are expected to be one solution to overcome the low interest of adolescents in social research. This community service activity was carried out in the youth scientific group (KIR) of SMAN 24 which consisted of 15 student members. The webinar activity was carried out in two sessions of material, among others about the urgency of social research and types of social research. The material is provided with an interactive lecture and discussion model so that the activities are two-way. Data collection was carried out in the form of an open questionnaire and pre-test-post-test. Data analysis with descriptive statistics and analysis of answers from open questionnaires. The results of the activity show that KIR member students have understood the urgency of social research and are able to express ideas to be developed into social research. Social research can be a positive activity for teenagers during a pandemic as a medium for self-development. In conclusion, this activity has been able to increase students' knowledge and understanding in social research. In addition, this activity has also developed critical thinking skills. ABSTRAK Artikel ini merupakan hasil dari kegiatan pengabdian kepada masyarakat yang bertujuan untuk meningkatkan pengetahuan remaja dalam penelitian sosial terutama di masa pandemic Covid 19. Bentuk kegiatan berupa webinar yang diharapkan dapat menjadi salah satu solusi untuk mengatasi rendahnya minat remaja dalam penelitian sosial. Kegiatan pengabdian masyarakat ini dilaksanakan pada kelompok ilmiah remaja (KIR) SMAN 24 yang terdiri dari 15 siswa anggota. Kegiatan webinar dilaksanakan dalam dua sesi materi antara lain tentang urgensi penelitian sosial dan jenis - jenis penelitian sosial. Materi diberikan dengan model ceramah interaktif dan diskusi agar kegiatan bersifat dua arah. Pengumpulan data dilakukan berupa angket terbuka dan pre test-post test. Analisis data dengan statistik deksriptif dan analisis jawaban dari angket terbuka. Hasil kegiatan menunjukan siswa anggota KIR telah memahami urgensi penelitian sosial dan mampu mengungkapkan ide untuk dikembangkan ke dalam penelitian sosial. Penelitian sosial dapat menjadi kegiatan positif bagi remaja pada saat pandemi sebagai media pengembangan diri. Kesimpulan dari kegiatan ini telah mampu menigkatkan pengetahuan dan pemahaman siswa dalam penelitian sosial. Selain itu kegiatan ini juga telah mengembangkan kemampuan berpikir kritis.